USPIO‐Enhanced MRI Neuroimaging: A Review. Issue 2 (3rd December 2015) - Gkagkanasiou, Maria; Ploussi, Agapi; Gazouli, Maria; Efstathopoulos, Efstathios P.
ABSTRACT: MRI is a powerful tool for the diagnosis and management for a variety of central nervous system (CNS) diseases. Ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles are a novel category of MRI contrast agents that seem to play a crucial role in the imaging of CNS. Due to their physical properties, USPIOs act as blood pool agents. USPIOs improve visualization of tumor vasculature and relative cerebral blood volume measurements, tumor‐associated inflammation, inflammatory‐immune mediated disorders, stroke and vascular malformations. Ferumoxytol, a new type of USPIO agent, appears to have ideal characteristics for the imaging of CNS. The last few years, ferumoxytol has been successfully used to image CNS neoplasms, CNS inflammations and cerebral malformations offering useful information on cellular and molecular level. In addition, ferumoxytol studies focused on the pathophysiology of other CNS disorders like multiple sclerosis and epilepsy are already in progress. Aim of this review article is to provide the potential role of USPIO‐enhanced MRI and the latest clinical applications of ferumoxytol agent in CNS imaging.